KEMAMPUAN KOMUNIKSI MATEMATIS SISWA SEKOLAH MENENGAH PERTAMA DAN MADRASAH TSANAWIYAH PADA MATERI FUNGSI DI P.BRANDAN KABUPATEN LANGKAT - Fadilah .; Dian Armanto; Asmin Panjaitan (Study Program of Mathematics Education of Unimed Postgraduate Program, 2010)
This research aim to to know ability of communications matematik student SMP/MTs through used by the study process teacher in teaching the function items. Study process told succeed to be seen from perception result concerning him succeeding learn in executing the study process as according to planning of specified study. Teacher run his function as counsellor and fasilitator so that can create the that active study. Beside teacher don't find the difficulty mean in executing the process study of good in the case of forwarding of items, domination of class and guide the student learn. Population in research is class student VIII from SMP/ MTS the in P.Brandan. With Cluster Random Sampling chosen become sampel is student SMP Negeri-2, student SMP Babalan, student SMP Ubudiyah, student MTs Darul Arafah and student MTs Al-Wasliyah. Research result indicate that the is student his study with co-operative with value categorize 3,45 hence told by theX the good enough study process. Sedangka the is student direct study with value categorize 2,97 told by the unfavourable study process. Pursuant to this research result, is suggested that by the teacher teach the mathematics in SMP/MTS can make study of co-operative as a(alternative in presenting Iesson of mathematics as well as can be improved toward domination of items, not merely orienting to solution of duty.